Manipulation of N-heterocyclic carbene reactivity with practical oriented electric fields. Issue 1 (8th December 2022) - Blyth, Mitchell T.; Coote, Michelle L.
Abstract : Electric fields can be used to tune the nucleophilicity and electrophilicity of N-heterocyclic carbenes and enhance their catalytic activity. Abstract : Using density functional theory (DFT) calculations, we demonstrate that the organocatalytic properties of NHCs, such as their nucleophilicity, electrophilicity and singlet triplet gaps, are predictably influenced by electric fields. These electric fields can be delivered in practical systems using charged functional groups to provide designed local electric fields, and their effects are strong enough to be synthetically relevant even in relatively polar solvents. We also show that these electrostatically enhanced NHCs elicit dramatic changes in the energetics of key transition states of a model benzoin condensation in various solvents, which can be tuned by the sign of the applied charge and the solvent polarity. Based on these findings, we suggest that NHCs are plausible candidates for electrostatic catalysts, and that electric field effects should be considered when designing NHC frameworks.